ANALISIS PERENCANAAN DAN PELAKSANAAN ANGGARAN DINAS PPAPP PROVINSI DKI JAKARTA - Mia Alfin Dahana (2020)
This study aims to determine the process of budget planning and budget execution. This research was conducted by the office of the empowerment of child protection and population control of DKI Jakarta Province. The method used in this research is qualitative with ethnometodology approach. The result of this study are the process of planning and implementing the budget carried out by the DPPAPP in accordance with existing procedures and regulations. However, even though it has been carried out accordance with procedures and regulations wich are fixed, there is still a suboptimal absorption of the budget, this is due to internal factors and external factors consisting of human resource for internal factor. The auction process and regulatory changes as an external factor.